2021
DOI: 10.1093/nar/gkab600
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical insight into the mechanism of dual CpG site binding and methylation by the DNMT3A DNA methyltransferase

Abstract: DNMT3A/3L heterotetramers contain two active centers binding CpG sites at 12 bp distance, however their interaction with DNA not containing this feature is unclear. Using randomized substrates, we observed preferential co-methylation of CpG sites with 6, 9 and 12 bp spacing by DNMT3A and DNMT3A/3L. Co-methylation was favored by AT bases between the 12 bp spaced CpG sites consistent with their increased bending flexibility. SFM analyses of DNMT3A/3L complexes bound to CpG sites with 12 bp spacing revealed eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…3 A ), but the influence of the outer flanks on activity increased with more and more disfavored inner flanks. In general, the effect of 3’ flanks was stronger than of the 5’ flanks, and often A/T bases were preferred at these places in agreement with our previous data ( 17 ). Interestingly, strong 5′ outer flank effects were only observed in the TGCCGTTG substrate which is missing the highly favored T(−2) residue.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…3 A ), but the influence of the outer flanks on activity increased with more and more disfavored inner flanks. In general, the effect of 3’ flanks was stronger than of the 5’ flanks, and often A/T bases were preferred at these places in agreement with our previous data ( 17 ). Interestingly, strong 5′ outer flank effects were only observed in the TGCCGTTG substrate which is missing the highly favored T(−2) residue.…”
Section: Resultssupporting
confidence: 92%
“…In the previous experiments shown in Figure 2A and 2B, flanking effects on CpG methylation were detectable also at the +4 to +7 positions. Related to this, in a previous study we showed strong effects of these sites on the co-methylation of CpG sites in a distance of 12 base pairs and found that A/T bases were preferred (17). We suspected that effects of these regions, which we now call "outer flanks", might have been partially masked by the stronger effects of the inner -3 to +3 flanks.…”
Section: Effects Of the Outer Flanksmentioning
confidence: 70%
See 2 more Smart Citations
“…However, it is interesting to note that the strongest methylation in our experiment was observed in the first CpG sites of our construct located up to 33 bp away from the nucleosome entry/exit site, which was not included in the cryo-EM structure. Different scenarios for the strong methylation of these sites are possible: Binding of the DNMT3A2 tetramer to these loci could occur without an interaction with the nucleosome core, in a manner described earlier for the interaction with free DNA 8 , 9 or by binding of a second tetramer side-by-side with the anchored complex as described recently 56 . On the other hand, it also appears possible for the complex to remain in the nucleosome-bound state and exploit the flexibility of the linker DNA and some hinge movement at the nucleosome binding site and perhaps within the DNMT3A2 tetramer to access the more remote sites.…”
Section: Discussionmentioning
confidence: 98%